Granulomatous Lymphocytic Interstitial Lung Disease in Infancy - Adetayo Adeleye; Margaret M Kelly; Nicola AM Wright; Weiming Yu; Mark A Anselmo (Canadian Respiratory Journal)
The authors report a case involving a child with chronic respiratory symptoms, who did not respond to conventional treatment. Low serum immunoglobin levels and pathological findings on lung biopsy revealed an unusual diagnosis for his age group. A specific treatment led to clinical improvement.